NALAR BAROKAH MADRASAH ANTARA FAKTA ATAU SUGESTI - Husnan Abrori (Universitas Islam Negeri Ar-Raniry, 2019)
Barokah is an integral part in the world of madrasah education, every second always appear the word from the academic community and customernya. The shift in the paradigm of contemporary education that places an educational output is the final process of transformation in the learning process in madrasah is sometimes broken by a public opinion that all processes are meaningless without baraka. The placement of the supernatural powers above a factual process has become a characteristic of madrasah education from the past to the present time, it is a belief that mensugesti all human beings and knock down the foundation of reasoning that education needs process and the carrying capacity in humanizing humanity or developing human potential accordingly nature that develops naturally and dynamically to suit the needs of the times. The cognitive ability that becomes the icon of life is no longer so urgent as a human driving pilot to fly higher to achieve success, let alone psychomotor no longer be a book to read in the curriculum of life, but different from affective is another face of barokah, in other words who is good ahlaknya then barokah no longer be sugesti and dreams perforated but a real dream that actualized in the success of life in the world and akherat.